2015
DOI: 10.1017/s0950268814003501
|View full text |Cite
|
Sign up to set email alerts
|

Acute gastrointestinal illness following a prolonged community-wide water emergency

Abstract: The drinking water infrastructure in the United States is ageing; extreme weather events place additional stress on water systems that can lead to interruptions in the delivery of safe drinking water. We investigated the association between household exposures to water service problems and acute gastrointestinal illness (AGI) and acute respiratory illness (ARI) in Alabama communities that experienced a freeze-related community-wide water emergency. Following the water emergency, investigators conducted a house… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Low water pressure and intermittent service provide opportunities for contaminant intrusion [ 26 ], resulting in microbial contamination and potentially increased risk for GII. Recent evidence from a documented water emergency in Alabama also found an association between self-reported GII and loss of water pressure and water service [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low water pressure and intermittent service provide opportunities for contaminant intrusion [ 26 ], resulting in microbial contamination and potentially increased risk for GII. Recent evidence from a documented water emergency in Alabama also found an association between self-reported GII and loss of water pressure and water service [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, respondents may not always be well informed about GII symptoms for other members of the household, especially other adults. Access to health care is limited in this underserved region [ 33 ] and other, potentially useful triangulating health data were unavailable at the time of study, a limitation noted in other studies of waterborne disease risk from similar settings [ 34 , 35 ] including from rural Alabama [ 27 ]. In another study from the same dataset [ 10 ], we reported that water pressure data were consistent between self-report and as-measured using pressure gauges at the time of sampling, though independent verification for other important measures we report are unavailable.…”
Section: Discussionmentioning
confidence: 99%
“…This study adds to the existing literature on how disturbances in the drinking water system may play a role in disease transmission in the U.S. Aside from community-wide water emergencies, wet weather events (e.g., precipitation, flooding) have also been associated with increased gastrointestinal illness. 17,31,32,[47][48][49][50] In addition, water pipes can become vulnerable with aging infrastructures and extreme temperature fluctuations. 16,51 Understanding the different risk factors involved can help water utilities and health departments establish and improve preparedness and response plans.…”
Section: Water Pipe Break and Acute Gastrointestinal Illnessmentioning
confidence: 99%
“…A case study from Alabama, US, looks at the effect of a freeze-related water emergency on diarrheal and respiratory illnesses. The researchers find a significantly higher risk of contracting diarrhea for households experiencing water disruptions and low water pressure and prevalence increases with the length of disruption (Gargano et al, 2015). The diarrhea outbreak in Milwaukee which affected 403,000 individuals, was caused by a filtration system that malfunctioned after a heavy storm releasing the bacteria Cryptosporidium oocysts in the water distribution system (Hoxie et al, 1997;Mac Kenzie et al, 1994).…”
Section: Figure 4: Distribution Of Willingness To Pay For Avoiding Pomentioning
confidence: 99%